Generic role of polymer supports in the fine adjustment of interfacial interactions between solid substrates and model cell membranes - Rossetti, Fernanda; Schneck, Emanuel; Fragneto, Giovanna; Konovalov, Oleg V.; Tanaka, Motomu (Langmuir, 2015)
To understand the generic role of soft, hydrated biopolymers in adjusting interfacial interactions at biological interfaces, we designed a defined model of the cell-extracellular matrix contacts based on planar lipid membranes deposited on polymer supports (polymer-supported membranes). Highly uniform polymer supports made out of regenerated cellulose allow for the control of film thickness without changing the surface roughness and without osmotic dehydration. The complementary combination of specular neutron reflectivity and high-energy specular X-ray reflectivity yields the equilibrium membrane-substrate distances, which can quantitatively be modeled by computing the interplay of van der Waals interaction, hydration repulsion, and repulsion caused by the thermal undulation of membranes. The obtained results help to understand the role of a biopolymer in the interfacial interactions of cell membranes from a physical point of view and also open a large potential to generally bridge soft, biological matter and hard inorganic materials.